2022
DOI: 10.3389/fnmol.2022.934820
|View full text |Cite
|
Sign up to set email alerts
|

Neuronopathic Gaucher disease: Beyond lysosomal dysfunction

Abstract: Gaucher disease (GD) is an inherited disorder caused by recessive mutations in the GBA1 gene that encodes the lysosomal enzyme β-glucocerebrosidase (β-GC). β-GC hydrolyzes glucosylceramide (GluCer) into glucose and ceramide in the lysosome, and the loss of its activity leads to GluCer accumulation in different tissues. In severe cases, enzymatic deficiency triggers inflammation, organomegaly, bone disease, and neurodegeneration. Neuronopathic Gaucher disease (nGD) encompasses two different forms of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 123 publications
(244 reference statements)
0
5
0
Order By: Relevance
“…Farfel-Becker et al used a mouse model of GD2 and observed that when the continuous neuronal accumulation of GlcCer reaches a certain level, a rapid cascade of neuroinflammation and neurodegeneration is induced in particular regions of the brain and may lead to neuronal cell death 78 , 79 . The symptoms of GD2 include progressive cognitive decline, muscle stiffness, loss of motor skills, difficulty in coordination, respiratory difficulties, and swallowing disorders along with the systemic manifestation of GD 80 , 81 . There are several phenotypes associated with GD2: hydrops fetalis- a condition when an excessive buildup of fluid in various parts of the body occurs; hepatosplenomegaly; skin abnormalities including congenital ichthyosis and abnormal, cellophane-like skin; dysmorphology of face features 82 ; neurological involvements such as joint contractures, decreased body movements, etc.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Farfel-Becker et al used a mouse model of GD2 and observed that when the continuous neuronal accumulation of GlcCer reaches a certain level, a rapid cascade of neuroinflammation and neurodegeneration is induced in particular regions of the brain and may lead to neuronal cell death 78 , 79 . The symptoms of GD2 include progressive cognitive decline, muscle stiffness, loss of motor skills, difficulty in coordination, respiratory difficulties, and swallowing disorders along with the systemic manifestation of GD 80 , 81 . There are several phenotypes associated with GD2: hydrops fetalis- a condition when an excessive buildup of fluid in various parts of the body occurs; hepatosplenomegaly; skin abnormalities including congenital ichthyosis and abnormal, cellophane-like skin; dysmorphology of face features 82 ; neurological involvements such as joint contractures, decreased body movements, etc.…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, its frequency is as high as 1:800 in Ashkenazi Jews ( 1 ). GD is caused by mutations in GBA1 (OMIM #606463), which encodes the lysosomal enzyme glucocerebrosidase (GCase) ( 2 ). To date, more than 500 mutations have been described in the GBA1 gene, including single base changes, splicing alterations, partial and total deletions, insertions, and rearrangements ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…GD is characterized by marked phenotypic and genotypic variability (D'Amore et al., 2021; Grabowski et al., 2021; Özdemir, 2022). Over 300 different mutations have been described for the GBA gene (D'Amore et al., 2021) and result in phenotypes ranging from asymptomatic to in‐utero death (Arévalo et al., 2022; Weinreb et al., 2021. Although GD phenotypes span a wide continuum, three types can be distinguished (Schiffmann et al., 2020; Silva García et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…GD is characterized by marked phenotypic and genotypic variability (D'Amore et al, 2021;Grabowski et al, 2021;Özdemir, 2022). Over 300 different mutations have been described for the GBA gene (D'Amore et al, 2021) and result in phenotypes ranging from asymptomatic to in-utero death (Arévalo et al, 2022;Weinreb et al, 2021. Although GD phenotypes span a wide continuum, three types can be distinguished (Schiffmann et al, 2020;Silva García et al, 2021). Type 1 GD (OMIM 230800) accounts for approximately 90% to 95% of all GD cases, with an estimated disease prevalence of 1 in 52,000 individuals in the general population (Biegstraaten et al, 2018;Chis, Chis, and Dumitrascu, 2021;Giraldo, 2021).…”
Section: Introductionmentioning
confidence: 99%